Medical learning in a private hospital: patients’ and companions’ perspectives - Sousa, Arthur de Carvalho Jatobá e; Tajra, Carolina da Rocha Machado; Coelho, Rodolfo de Souza; Gomes, Ciro Martins; Teixeira, Ricardo Afonso (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: Contact with patients has important implications for medical students’ education. Previous studies have shown that patients in teaching hospitals have positive views about medical education. The aim here was to assess the acceptability of medical education among patients and their companions in a non-teaching private hospital that is planning to implement a medical teaching program in the near future. DESIGN AND SETTING: Cross-sectional study conducted in a 200-bed tertiary-care private hospital in Brasília. METHODS: Between March and April 2005, patients and their companions in three different sections of the hospital (intensive care unit, ward and emergency waiting room) were surveyed using a questionnaire. RESULTS: The questionnaire was completed by 209 volunteers. The majority of the volunteers (178; 85%) said that they would allow a student to be present during consultations. Of these, 102 (57%) said that they would like to have a student present. Acceptance of the presence of students was higher among males (males 93%; females 81%; P = 0.026). Intensive care unit respondents said that they would like medical students to be present more frequently than the other two groups said this (ward 48%; emergency room 49%; intensive care unit 74%; P = 0.011). CONCLUSIONS: Not only were medical students well accepted but also their presence during consultations was desired by many patients and their companions. These findings may be of great value for plans to implement medical teaching programs in private hospitals.